Destinación Casa. 2024 Buenos Aires, Argentina - Santillan Messina, Vanesa (ARQ (Santiago, Chile), 2025)
In response to the paradox of downtown Buenos Aires-where overcrowded tenement housing coexists with vacant office buildings-this thesis project proposes transforming an unused government building into cooperative housing for migrants. Inspired by the collective logic of the conventillo, but updated to contemporary needs, the design brings together spaces for living, working, and gathering in a proposal where architecture is placed at the service of social and urban integration.